High power narrow-linewidth Raman amplifier and its limitation - Distler, Victor; Moeller, Friedrich; Strecker, Maximilian; Palma-Vega, Gonzalo; Walbaum, Till; Schreiber, Thomas; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
We investigated the limitations in output power generated by a high power narrow-linewidth Raman fiber amplifier. The pump was produced by a kW-level all-fiber Yb-doped amplifier emitting at 1060 nm, whose seed linewidth could be changed. The Raman seed was a narrow-linewidth signal at 1110 nm co-propagating with the laser at 1060 nm. The main Raman conversion occurred in the passive fiber at the amplifier output. We identified cross-phase modulation (XPM) as a main reason for broadening of the Raman light by using different pump sources, which is a first limitation. An improved setup was limited at approximately 600 W of Stokes output power by a threshold-like onset of a transverse mode instability. Since the instability was not observed without a Stokes seed and the temperatures of the active fiber with and without Stokes seed are equal, this constitutes the first direct observation of transverse mode instabilities (TMI) induced by SRS in a passive fiber.
CRIS-Team Scopus Importer:2023-04-20
Keywords: High power fiber lasers; Raman laser; Stimulated raman scattering